1997
DOI: 10.1379/1466-1268(1997)002<0041:tpkisu>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The protein kinase inhibitor SB203580 uncouples PMA-induced differentiation of HL-60 cells from phosphorylation of Hsp27

Abstract: HL-60 cells are an attractive model for studies of human myeloid cell differentiation. Among the well-examined parameters correlated to differentiation of HL-60 cells are the expression and phosphorylation of the small heat shock protein Hsp27. Here we demonstrate that PMA treatment of HL-60 cells stimulates different MAP kinase cascades, leading to significant activation of ERK2 and p38 reactivating kinase (p38RK). Using the protein kinase inhibitor SB 203580, we specifically inhibited p38RK and, thereby, act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…However, the p38 MAPK inhibitor SB203580 could prevent PMA-induced Hsp27 phosphorylation, but did not abrogate differentiation, making it unlikely that Hsp27 phosphorylation is absolutely required for PMA-induced HL-60 cell differentiation [145]. Other studies have reported altered Hsp27 protein levels in differentiated cells [23,24,47,102], but few have addressed the correlation with changed Hsp27 phosphorylation [10,136].…”
Section: Cell Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the p38 MAPK inhibitor SB203580 could prevent PMA-induced Hsp27 phosphorylation, but did not abrogate differentiation, making it unlikely that Hsp27 phosphorylation is absolutely required for PMA-induced HL-60 cell differentiation [145]. Other studies have reported altered Hsp27 protein levels in differentiated cells [23,24,47,102], but few have addressed the correlation with changed Hsp27 phosphorylation [10,136].…”
Section: Cell Differentiationmentioning
confidence: 99%
“…Because PMA-induced differentiation of HL-60 cells was correlated with increased expression and phosphorylation of Hsp27, it was speculated that phosphorylation of Hsp27 is required for differentiation [145]. However, the p38 MAPK inhibitor SB203580 could prevent PMA-induced Hsp27 phosphorylation, but did not abrogate differentiation, making it unlikely that Hsp27 phosphorylation is absolutely required for PMA-induced HL-60 cell differentiation [145].…”
Section: Cell Differentiationmentioning
confidence: 99%
“…Stress related phosphorylation and dephorphorylation of hsp27 is catalyzed by enzymes of the p38-MAPK pathway [13,14]. Since specific pharmacological inhibitors of this signaling pathway are available they have been used to study the phosphorylation processes of hsp27 [15,16]. Unphosphorylated hsp27 forms large multimers, whereas its phosphorylation results in complex dissociation, altered protein binding [17,18] and loss of chaperoning activity [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Unphosphorylated hsp27 forms large multimers, whereas its phosphorylation results in complex dissociation, altered protein binding [17,18] and loss of chaperoning activity [19,20]. Hsp27 can be phosphorylated reversibly on three serine residues (15,78,82) by the mitogenactivated protein kinase-activated kinases 2 and 3 (MK2/3), which are activated through the p38 signaling pathway [21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, geldanamycin, an inhibitor of Hsp90, blocks kinase-mediated signaling events during T-lymphocyte activation (Schnaider et al 2000). Gaestel and coworkers (Schultz et al 1997) provided evidence that p38RK and MAPKAP kinase 2 are part of a signal transduction pathway leading to Hsp27 phosphorylation in HL-60 cells but that this phosphorylation event is not needed for HL-60 cell differentiation. A number of papers have added to our understanding of induced cytoprotection (thermotolerance), links between the stress response and apoptotic pathways, and blocking of signal transduction pathways.…”
Section: Introducing Professor Nikki Holbrook Stress Signaling and Amentioning
confidence: 99%